Genotype and organ effect on the occupancy of phyllosphere prokaryotes in different rice landraces - Yeo, Freddy Kuok San; Cheok, Yin Hui; Wan Ismail, Wan Nurainie; Kueh-Tai, Felicia Fui; Lam, Tommy Tsan-Yuk; Chong, Yee Ling (Springer Nature, 2022)
Bacteria community provides essential ecological services to rice plants. The bacterial diversity of rice varies across host plant genotype and organs. This study employed 16S rDNA amplicon sequencing to characterise the bacterial community associated with three rice landraces using leaf blade and stem samples. The prokaryotic community found in these rice landraces comprised of two kingdoms, 12 phyla, 25 classes, 40 orders, 80 families, and 118 genera. Proteobacteria (53.9%) was the most abundant phylum. The most abundant genus was an undefined genus under Cyanobacteria (33.0%). Homogeneity of prokaryotic community was observed across the three rice landraces, which may suggest a high similarity in biological and genetical properties of the rice landraces. The difference in prokaryotic composition between leaf blade and stem was depicted based on principal coordinate analysis. This study observed that the prokaryotic inhabitants in rice plants is predominantly determined by rice plant organs.